Engineering complex muscle-tissue interfaces through microfabrication. (12th June 2019) - Arrigoni, Chiara; Petta, Dalila; Bersini, Simone; Mironov, Vladimir; Candrian, Christian; Moretti, Matteo
Abstract: Skeletal muscle is a tissue with a complex and hierarchical architecture that influences its functional properties. In order to exert its contractile function, muscle tissue is connected to neural, vascular and connective compartments, comprising finely structured interfaces which are orchestrated by multiple signalling pathways. Pathological conditions such as dystrophies and trauma, or physiological situations such as exercise and aging, modify the architectural organization of these structures, hence affecting muscle functionality. To overcome current limitations of in vivo and standard in vitro models, microfluidics and biofabrication techniques have been applied to better reproduce the microarchitecture and physicochemical environment of human skeletal muscle tissue. In the present review, we aim to critically discuss the role of those techniques, taken individually or in combination, in the generation of models that mimic the complex interfaces between muscle tissue and neural/vascular/tendon compartments. The exploitation of either microfluidics or biofabrication to model different muscle interfaces has led to the development of constructs with an improved spatial organization, thus presenting a better functionality as compared to standard models. However, the achievement of models replicating muscle-tissue interfaces with adequate architecture, presence of fundamental proteins and recapitulation of signalling pathways is still far from being achieved. Increased integration between microfluidics and biofabrication, providing the possibility to pattern cells in predetermined structures with higher resolution, will help to reproduce the hierarchical and heterogeneous structure of skeletal muscle interfaces. Such strategies will further improve the functionality of these techniques, providing a key contribution towards the study of skeletal muscle functions in physiology and pathology.